Boosting current output of triboelectric nanogenerator by two orders of magnitude via hindering interfacial charge recombination. (November 2021) - Firdous, Irum; Fahim, Muhammad; Wang, Lingyun; Li, Wen Jung; Zi, Yunlong; Daoud, Walid A.
Abstract: The performance of triboelectric nanogenerator is limited by interfacial charge losses due to alternate charge transfer. This is usually suppressed by addition of electron blocking, electron transporting layers or through external excitation. However, these approaches screen only electrons from the interface while the unstable positive charges remain. Herein, we report a stable tribopositive layer with an overall positive surface and embedded magnetic active negative centers for stabilizing positive charges to prevent cation recombination with anion of counterpart. Besides, a counterpart with high electron delocalization density is used for screening interfacial negative charges, leading to enhanced charge accumulation of 11 nC with short circuit current of 0.8 µA, increasing to 54 nC and 17.4 µA by staking 4 units of 2.25 cm 2 device in alternate layered structure, with an enhancement rate of 15.1 nC and 5.6 µA per unit. Further, the embedded negative centers in response to magnetic field form skewed charge transporting channels, causing homogeneous distribution of potential on the tribopositive layer, effectively transporting charges to electrode via hindering bulk losses. The single unit shows 15, 900% enhancement reaching 4.8 µA, 208 µC m −2 and 1.66 W m −2 and demonstrating the highest enhancement capacity compared to previously reported strategies and thus a promising potential for wearable electronics with high power demand. Graphical Abstract: Output current of triboelectric nanogenerator is boosted by two orders of magnitude through aligned positive potential surface on tribopositive layer with embedded negative centers. The aligned surface potential causes effective charge transfer and the negative centers stabilize the positive charge after losing electrons, thereby, hindering interfacial change recombination, which results in 15, 900% enhancement in current with a surface charge density of 208 µC m −2 . ga1 Highlights: Development of P/Fe3 O4 as electron donor and cation screener from contacting interface. Dual triboelectric behavior of P/Fe3 O4 is evaluated for the first time through potential mapping. Effect of P/Fe3 O4 on surface potential & energy band alignment during charge transfer is presented. Device output of 11 nC & 0.8 µA (0.26 W m −2 ) is enhanced to 54 nC & 17.3 µA (0.6 W m −2 ) by stacking 4 units. Fe3 O4 regions skew in response to magnetic field, hindering bulk losses reaching 204 µC m −2 (1.66 W m −2 ).